In Silico Study of Antidiabetic Activity Mikania Cordata as PPAR- γ Agents - Oktavianti, Dian; Masriani; Arief, Ihsanul (Universitas Pendidikan Mandalika, 2025)
Diabetes mellitus remains a significant global health problem, requiring safer and more effective therapeutic agents. Peroxisome Proliferator-Activated Receptor gamma (PPAR-γ) plays a crucial role in regulating glucose metabolism by enhancing insulin sensitivity, making it a key target in the development of antidiabetic drugs. Pioglitazone, a PPAR-γ agonist from the thiazolidinedione class, has long been used as a conventional therapy; however, its long-term use is associated with side effects such as fluid retention, weight gain, and an increased risk of heart failure. The World Health Organization recommends the development of natural-based drugs with minimal adverse effects. One promising plant candidate is Mikania cordata, which has been reported to possess antidiabetic activity and contains various bioactive compounds, including terpenoids, flavonoids, sterols, and sesquiterpenoids. This study aimed to evaluate the bioactive compounds of Mikania cordata as potential natural PPAR-γ agonists using a molecular docking approach. A total of 36 ligands from M. cordata were docked to the PPAR-γ protein (PDB ID: 2PRG), with Pioglitazone serving as the positive control. Docking was performed using PyRx with the AutoDock Vina system after ligand and protein preparation with UCSF Chimera 1.16. The docking results were analyzed using BIOVIA Discovery Studio Visualizer to identify the interactions between the ligand–protein complexes. The results showed that Cordatolide exhibited the lowest binding affinity (–9.1 kcal/mol), followed by Stigmasterol (–8.9 kcal/mol), both of which were better than Pioglitazone (–8.8 kcal/mol). Interaction analysis revealed that Cordatolide formed two hydrogen bonds with key residues ARG288 and GLY284, accompanied by stable hydrophobic interactions without any unfavorable contacts. Meanwhile, Stigmasterol also showed competitive affinity, although its stability relied solely on hydrophobic interactions without hydrogen bonding. Therefore, Cordatolide demonstrates strong potential as a natural PPAR-γ agonist with fewer side effects compared to conventional therapies. This study provides a novel finding on the potential of M. cordata as a natural PPAR-γ agonist; however, further in vitro and in vivo evaluations are required to confirm its pharmacological activity.